- ANALISIS PENYERTAAN PELAKU TINDAK PIDANA JUDI TOGEL ONLINE : - - Jozevin Elizabeth; Ermania Widjajanti (Faculty of Law, Universitas Trisakti, 2024)
Propels within the world of data and innovation have given birth to a better approach of betting, specifically online betting. This new method gives rise to numerous troubles in revealing a web betting case, both to decide the culprit of online betting and to decide the put and time of the occurrence as well as legitimate obligation for the culprit of online betting. The detailing of the issue is what frame the culprit of the criminal act of online lottery betting takes. The inquire about strategy was carried out normatively with the nature of the inquire about utilizing expository expressiveness, the sort of information utilized was auxiliary information, subjective information investigation and conclusion drawing based on the deductive rationale strategy. The comes about of the inquire about and talk are the reality that individuals working closely together to carry out unlawful acts is the foremost critical angle, and it is conceivable that typically the greatest portion of being a portion of carrying out these acts. In this case, the shape of support utilized is the individual who took portion in carrying out the activity. The conclusion is Participation in this scenario will take the form of a Participating Person (Medepleger).